MAKNA HIATUS DALAM HADIS: TELAAH ATAS KONSEP ISTIRAHAT DAN JEDA DALAM KEHIDUPAN MUSLIM: Makna Hiatus Dalam Hadis: Telaah Atas Konsep Istirahat Dan Jeda Dalam Kehidupan Muslim - Hafid Khoirum Majid; Azis Arifin; Muhammad Alif (Institut Agama Islam Sumatera Barat Pariaman, 2025)
Modern life is characterized by increasing activity pressures, productivity demands, and a fast-paced pace, resulting in increasingly neglected spaces for pause and rest. This situation raises the need to revisit the concept of hiatus as an essential part of maintaining a Muslim's physical, mental, and spiritual balance. This article aims to examine the concept of hiatus in the hadith through a thematic approach (maudhu'i) to authentic hadiths related to rest, self-reflection, i'tikaf, 'uzlah, and time management. The selected hadiths are grouped by theme and analyzed through their historical context and spiritual values. The results show that according to the hadith, hiatus is not simply a cessation of activity, but rather a practice of spiritual awareness that serves to awaken self-clarity, strengthen the relationship with God, and balance the physical-spiritual rhythm. Its application is evident in traditions such as i'tikaf, voluntary sleep, reading, and directed solitude. The study also found that uncontrolled hiatus has the potential to lead to laziness, neglect of responsibilities, and social alienation. This finding implies that the concept of hiatus in the hadith can be used as a basis for developing self-management and spiritual health for modern Muslims.